(untitled) (Research, Society and Development, 2020)
The fishing activity on the Amazonian coast is heterogeneous, both in the ichthyofauna of commercial importance and in the methods of catch. In view of the diversity of fishes, there is the Ranchycentron canadum Cobia, a pelagic, migratory species, of medium to large size, landed along the coastal municipalities of Pará. Therefore, the study aimed to describe the fishing incident under this species and variation along time, in addition to determining CPUE (Catch per Unit effort) and periodic cycles, using effort and capture data provided by the Estatpesca program. The applied methodology consisted of exploratory data analysis, application of the cluster analysis, to verify the possible landing relations between the municipalities, the relations of the catch with the effort were performed through Pearson’s correlation, and the CPUE correlation used by through linear correlation and through this estimate, we verify, through wavelet analysis, the possible existing periodic cycles. The CPUE time series of the Cobia was performed using the PCNM method, however, using the Mann Kendall test, it did not show a significant trend. The municipality of São João de Pirabas was the main landing point of the species, in other municipalities they are occasional. The CPUE identified in this study was the average of the capture of small boats that used the serreira net in relation to the average number of fishermen (r = 0.48) and through this estimate of Cobia abundance, periodic cycles were identified 11.3 months.